Wastophobia: A Path Towards Sustainability in Responsible Behavior-A Case of Domestic Sector Electricity Waste Management - Hanif, Muhammad Wasif; Hafeez, Shakir; Iqbal, Naveed; Shah, Syed Afzal Moshadi; Afridi, Muhammad Asim (International Journal of Energy Economics and Policy, 2021)
Electricity is indispensable for socio-economic developments. Its demand is dramatically increasing in the domestic sector at an incredible pace despite distressing electricity deficiency in most of the world's developing economies like Pakistan. The synthesis of the literature portrays that domestic consumers irresponsibly (consciously or unconsciously) waste a major portion of their electricity consumption that is detrimental to electricity security, climate, and sustainable developments. To effectively deal with the issue of electricity waste, this study is presenting a theoretical research framework containing a fear based promotional marketing strategy. The novelty of the model is to present an intriguing behavioral strategy for developing consumer sustainable responsible behavior. Confronting consumers with the awareness of wasteful consumption and its detrimental conditional impacts (financial, environmental, personal future & electricity security threats and religious punishments) can significantly create threats of electricity wastage (wastophobia) in the electricity consumers' mind. Wastophobia strategy will set ground foundations for the researchers and policymakers to manage electricity waste as well as wastage of other goods & services. This strategy will significantly contribute to the theoretical knowledge of various disciplines, such as marketing, psychology, waste management and so on. Sustainable responsible behavior is categorically supporting consumers as well as holds huge potential in present policy guidelines under the arena of electrical purification and waste management. Moreover, such policy implications are viable, sensible, and supportive for national electrical transmission and production regulatory authorities at both public and public counterparts. Keywords: Energy Efficiency, Wasteful Consumption Awareness, Religious Sermons, Wastophobia, Sustainable Responsible Behavior JEL Classifications: Q4, Q40, D1 DOI: https://doi.org/10.32479/ijeep.11450